Hauptstadt und Hauptstadtregion im System der lokalen Gebeitskörperschaften - Mäeltsemees, Sulev (Estonian Discussions on Economic Policy, 2017)
The purpose of this paper is to analyze the position of capital city and capital city region in Estonia. An analysis of the position of the capital city in the local self-government organisation of a country must consider the following four aspects: 1. The capital city in the system of human settlements. 2. The capital city and the national legal environment, including the capital city’s relationship with the central government and regional co-operation. 3. Management models of the capital city, including decentralisation. 4. The economic environment in the capital city; the capital city and the economic environment of the region and the country. The author is of the opinion that there are practically no interdisciplinary analyses addressing legal, economic, and demographic and management problems of capital city in Estonia.